South Africa’s Xenophobia: Can Thabo Mbeki Change the Narrative? CODESRIA Bulletin Online, No. 6, July 2026 - Yusuf Bangura, (CODESRIA Bulletin, 2026)
President Thabo Mbeki’s lecture during a high-level business breakfast on 22 May 20261 was a major pushback against the current xenophobia by black South Africans against African immigrants—a phenomenon that has generated the term ‘Afrophobia’. The lecture systematically highlighted the heroic contributions of Africans to the anti-apartheid struggles, urging his compatriots to reckon with this history and change course. In this lecture, Mbeki recollected his vast experiences in various African countries when the ties between the ANC and Africa were unbreakable. For decades, the continent viewed its own independence as incomplete as long as minority white rule persisted in South Africa. Mbeki noted that in the first two decades of South Africa’s liberation, the vision of the ANC government was to embed South Africa’s development within a pan-African integration framework that would see South Africa and the rest of Africa prosper together. He regretted that there had been a serious regression of the pan-African spirit in South Africa in the past twenty-five years. In a sharp rebuke, he accused his compatriots, who are attacking African immigrants and blaming them for South Africa’s high level of black unemployment, of chasing the wrong target, or as he put it, ‘chasing ghosts’. It’s good to see that Mbeki, a former president, who spent many years in other African countries, including Nigeria and Tanzania, is speaking out against the ugly spectre of xenophobia that has gripped South Africa. The only other prominent South African politician who has denounced his country’s xenophobia is Julius Malema. Malema speaks boldly and clearly against the obnoxious, white-operated apartheid system that devalued Africans, and doesn’t hold back from calling out the ANC for its dismal failure to correct the problem and improve the lives of black South Africans. In this article, I analyse the multifaceted contributions of Africa to South Africa’s liberation from apartheid, the numerous harrowing cycles of xenophobia in South Africa, and the folly of blaming African immigrants for black South Africans’ high levels of unemployment. I trace the black unemployment problem to the apartheid regime’s race-driven model of development that prioritised capital-intensive industrialisation, as well as the abject failure of the ANC government to change course and set South Africa on a growth path that uplifts the majority of its population. I conclude with a discussion of how South Africa’s major parties use anti-immigrant narratives for electoral gain, and of the pushback against this tactic from civil rights groups. Ultimately, I call for teaching the social history of Africa’s contributions to the anti-apartheid struggles, across South African schools and tertiary institutions, to repair the country’s damaged reputation with the rest of the continent. Africa and the Struggle to Liberate Black South Africans People of my generation treated the oppression of black South Africans as an attack on our identity. We viewed the struggle against apartheid as a non-negotiable African burden. We were all in it together, irrespective of how far we were from the field of action. We gave speeches, marched in London and made financial contributions. During my time in Nigeria in the 1980s, the liberation of Southern Africa was vigorously canvassed by all strata of society—students, academic staff, labour unions and other organised interests. We were ready to give everything to actualise what seemed at the time like an impossible task. South Africa’s neighbours—such as Tanzania, Zambia, Angola, Mozambique and Zimbabwe—acted as frontline states and provided a home for the ANC and the Pan-African Congress from which they could conduct their campaigns (Evans 1984/85). These states were exposed to costly and destabilising South African cross-border raids, proxy warfare and, in the case of Angola, a momentous war with the South African army (the SADF), which culminated in the defeat of the SADF by Angolan and Cuban forces in the Battle of Cuito Cuanavale in 1987–1988. That defeat, which we celebrated in Nigeria, broke the myth of white South African invincibility. Headquartered in Dar es Salaam, the Organisation of African Unity—the original name of the African Union—created the African Liberation Committee and the Liberation Fund, with mandatory contributions from member states to finance the purchase of weapons, uniforms, medicines and radio equipment for the South African liberation movements. And countries like Tanzania, Zambia, Ghana and Nigeria issued thousands of travel documents to exiled South Africans, allowing them to travel and build support for their campaigns. The contribution to the anti-apartheid struggle by Nigeria, one of the countries that has been viciously targeted by South African xenophobes, needs emphasis. Despite being thousands of miles away from the conflict zone, Nigeria was declared a frontline state by the OAU because of its enormous contribution to the struggle. The country established a Southern Africa Relief Fund, which attracted donations not only from the government but also from citizens. Nigerian civil servants contributed 2 per cent of their salaries to that fund. Nigeria also issued more than 300 passports to black South Africans to facilitate their overseas travels. Writing on the online platform of the South African Institute of International Affairs (SAIIA), Nomfundo Ngwenya (2010) reported that Nigeria had spent an estimated USD 61 billion in supporting the frontline states by the end of apartheid in 1994. This figure may be exaggerated, but it does underscore the country’s immense contribution to the liberation of black South Africans. These noble efforts were backed by ordinary citizens across the continent, who actively humanised the anti-apartheid struggle—performing songs and plays, organising marches and welcoming exiled South Africans into their homes and communities. When thousands of black South Africans fled the country following the brutal suppression of the 1976 Soweto Uprising, African governments across the continent offered scholarships to them to ensure that a free South Africa would benefit from an educated class of administrators, doctors, engineers and other professionals ready to govern. African artists and writers complemented these initiatives by using media platforms to amplify the message of anti-apartheid icons like Nelson and Winnie Mandela, and Steve Biko, keeping their plight alive in global discussions. Surely, without the institutional activism of the OAU, the strategic actions of the frontline states and the financial sacrifices of countries like Nigeria, the internal resistance within South Africa would have been profoundly isolated. It would not have been enough to end white minority rule. The point, therefore, is simple: apartheid’s fall was not just a domestic triumph by black South Africans; it was clearly a crowning victory for pan-African solidarity. Although Mbeki didn’t cover all this ground in his speech, this was the message he wanted to convey to his compatriots and Africans at large. But will his speech make a difference? Will it compel the ANC government, which has been soft on the rhetoric and violence of xenophobic groups, to change direction? Will it empower civil rights groups to forcefully take on the xenophobes? And will it spark a deep rethink in South Africa about how it should engage with the rest of the continent in tackling its problems of unemployment, urban poverty, xenophobia and social exclusion? Harrowing Cycles of Xenophobia It is important to stress that even though Mbeki is now speaking out against the xenophobia of his compatriots, he steadfastly refused to condemn the violent attacks on immigrant Africans as xenophobic when he was president between 1999 and 2008. He instead labelled the attacks as “naked criminal activity” perpetrated by a few rogue elements (Staff Reporter, 2008). Major, nationwide outbreaks of xenophobic violence in South Africa made global headlines in 2008 and 2015. However, targeted attacks against African immigrants can be traced back to 1994–95 (South Africa History Online 2023), the dawn of black majority rule. In January 1995, in Alexandra, a township just outside Johannesburg, gangs of armed youth destroyed the homes and properties of migrants from Zimbabwe, Mozambique and Malawi in a violent campaign dubbed Buyelekhaya (Go Back Home). The migrants were forcibly marched to local police stations to demand their immediate deportation. These types of violent incidents, which were frequent in the 1990s, exploded in 2008 into an organised, nationwide crisis, which started in Alexandra before engulfing seven of South Africa’s nine provinces. Sixty-two people died, thousands were injured, and tens of thousands of immigrants were displaced. The military had to be deployed to restore order. Just a year later, in 2009, another massive attack against immigrants in the Western Cape resulted in about 3,000 Zimbabwean farmworkers being violently chased from their homes and their properties looted and burned. In 2015, after the Zulu king, Goodwill Zwelithini, announced that foreigners should ‘pack their bags and go’ (Davis 2015), at least seven people were reportedly killed, hundreds were injured, and foreign governments such as Malawi and Somalia had to repatriate their citizens. Xenophobic violence against immigrants persisted in 2016–17 (the Tshwane and Pretoria riots) and 2018 (the Durban and Johannesburg riots), leading to the rise of organised vigilantism in 2021. Indeed, 2021–25 marked a distinct shift from spontaneous rioting to organised anti-immigrant campaigns. The first such organised campaign was Operation Dudula (‘push back’ or ‘drive out’, in isiZulu). Launched in 2021, the movement conducted door-to-door raids in townships, demanding to see visas, evicting foreign traders and clashing with police (Myeni 2024). By 2024, these groups started blocking migrants from accessing hospitals and schools, prompting local courts to issue emergency injunctions against them. The latest cycle of xenophobic violence began around April and May 2026. It was triggered by a vigilante movement known as ‘March and March’ and led by Jacinta Ngobese-Zuma, a former radio presenter, who organised large-scale demonstrations in major cities like Durban, Johannesburg and Pretoria (O’Reagan, Reitumetse and Nkosi 2026). The demonstrations later fragmented into violent vigilante actions, with mobs attacking African immigrant-owned shops with whips and stun guns, and driving migrants out of communities. The violence escalated further when mobs began actively preventing migrants from entering schools and hospitals. Matters came to a head in early June when anti-migrant groups circulated a highly publicised notice, warning all undocumented migrants to leave the country by 30 June or face mass action. African immigrants, including those with residence permits, felt traumatised—the mobs were targeting all African immigrants, legal and illegal. The government didn’t stop the violence or protect even legitimate immigrants. Several neighbouring countries (such as Malawi and Mozambique) initiated emergency bus repatriations, and Ghana and Nigeria organised flights to evacuate their citizens. Scapegoating African Immigrants when the Culprits for Black Dispossession and Unemployment are in Plain Sight It is important to put the ‘migrant crisis’ in perspective to underscore the folly of blaming African immigrants for the woes of black South Africans. African immigrants contributed significantly to the development of South Africa, as imported labour from neighbouring countries. Driven by the mining industry, the apartheid regime operated a well-organised, state-backed migrant labour system managed by the Witwatersrand Native Labour System. In the gold and coal mines, the vast majority of the workforce was often foreign-born Africans. In the 1970s, an astonishing 80 per cent of the total mining labour force was drawn from neighbouring countries (Vletter 1987), with nearly 500,000 men primarily from Lesotho, Mozambique and Malawi working in the mines at any given time. In his seminal 1972 article, ‘Underdevelopment and Dependence in Black Africa: Origins and Contemporary Forms’(1972), the influential Egyptian political economist, Samir Amin, captured the importance of this immigrant labour in his labour reserve framework, which explained how the apartheid state relied on a pool of rural and foreign African labour to feed the mines and transform South Africa into a sub-centre in global capitalism. Yet, migrants account for only 4.1 per cent of South Africa’s population, and foreign-born workers make up 8.9 per cent of the labour force. Therefore, even if all African immigrants left the country, the vast majority of the 43.7 per cent of South Africans who are reportedly unemployed would still be without work. In addition, citing data from a 2018 World Bank report, a South African social activism group, Collective Voices for Health Access (2025), reported that employing one immigrant worker yields two jobs through multiple business activities. Migrants create their own jobs in retail, tailoring, food services and repairs, and provide jobs to black South Africans and incomes to black South African suppliers and landlords. What then is the problem? It has been well documented that South Africa’s incredibly high unemployment is a legacy of the apartheid regime’s race-driven industrialisation strategy (McCarthy 2005; Bell and Madula 2001; Moritz 1994; Seekings and Nattrass 2005 and 2015). In the early 20th century, the South African state actively intervened to secure cheap, unskilled black labour for mines and agriculture while protecting high white wages. Because of the global boycott against apartheid, the economy industrialised largely by producing goods for the domestic market. But this market was severely constrained because the black majority lacked purchasing power. Factories quickly reached their growth limits and failed to scale up to generate mass employment. By the 1960s and 1970s, the economy began shifting towards a capital-intensive and skill-intensive growth path, especially when the regime prioritised heavy industries (chemicals, steel, arms and energy), which were inherently capital-intensive. The result was unmistakeable: by the 1970s and 1980s, fixed capital per worker in manufacturing grew by 4.6 per cent annually (Moritz 1994), meaning that factories were investing in machines to replace workers rather than expanding payrolls. As industries mechanised, the demand for unskilled labour plummeted, while the demand for skilled labour grew. Furthermore, through its racist labour laws, the state reserved skilled and semi-skilled jobs exclusively for the white minority. But there were not enough white workers. A permanent structural mismatch was created: a severe shortage of skilled workers coexisting with a massive surplus of unskilled workers (Seekings and Natrass 2005). Instead of training and promoting black workers, many businesses chose to automate tasks. This anti-black worker policy systematically choked off the entry-level manufacturing jobs that countries like those in East Asia created to uplift their populations. Indeed, by deliberately undereducating the majority black population, the apartheid state ensured that millions of black South Africans were structurally excluded from participating in the economy when it modernised and required more literate, semi-skilled industrial workers. The tragedy of the last thirty-two years of black-majority rule is the abject failure of the ANC to dismantle this debilitating system and set South Africa on a growth path that uplifts the majority of its population. Instead, millions of black South Africans are now myopically directing their anger at African immigrants—the very people who formed their core support base during their struggle for freedom. The ANC’s massive liberalisation strategy between 1994 and 2008, which encouraged white corporate capital to transfer profits overseas, further compounded the problem (Bond 2005). In addition, employers reacted to the ANC policy of paying high wages to a small portion of the workforce and defending workers’ rights by further mechanising, automating, or shedding jobs entirely (Seekings and Nattrass 2005).The new government’s pro-black industrial strategy, Broad-Based Black Economic Empowerment (BBBEE), largely benefited the black middle class, leaving most urban blacks trapped in townships that reek of atrocious living conditions and crime. When my wife and I visited Cape Town in 2024, we were shocked at the grossly inhuman levels of racial inequality in living standards. Massive, immaculate, white-owned houses with dreamlike swimming pools and high electric fences in leafy neighbourhoods contrasted with more than 400 high-density townships with tin shacks and poor sanitation. The difference was mind-boggling, depressing and obscene. Khayelitsha, a township of about two million black people2, sandwiched between the overwhelmingly white, opulent Stellenbosch and Cape Town, is utterly disgraceful. Blue, makeshift plastic structures serve as communal toilets in parts of the township. It should be noted that the income ratio between white and black South Africans is 9.3:1 and a typical black household holds less than 5 per cent of the wealth of a typical white household. I wondered aloud how the party of black liberation, the ANC, could tolerate such inequalities, and how long it would take for the black population to actively and uncompromisingly demand change and reverse the situation. Instead, black anger is now directed at foreign blacks who play no role in their oppression. The sociological literature on ‘black-on-black violence’ in racially segregated societies throws considerable light on this phenomenon. When a racial group is subjected to severe systemic deprivation, humiliation and violence by a dominant racial group, it feels entirely powerless to strike upwards at its true oppressors, who are protected by segregated spaces and fortified gates. Instead, the frustration and anger caused by this powerlessness is released ‘horizontally’, against those closest and deemed to have fewer rights, such as African immigrants (Freire 1970; Bauer et al. 2021) Conclusion It is dispiriting to see large sections of South Africa’s black population blame African immigrants for their poor job prospects. It is even more painful to observe leading political parties, such as uMkhonto weSizwe (MK) Party, led by Jacob Zuma—a former ANC leader and president of South Africa—anchor their political strategy of winning seats from the ANC on a virulent anti-immigrant platform. This party, the third largest in parliament, as well as the Patriotic Alliance led by Gayton McKenzie and Herman Mashaba’s ActionSA, have been heavily linked to the March and March movement (O’Reagan et al. 2026). The MK Party had even announced that it would participate in the mass anti-immigrant demonstrations scheduled for 30 June. As many South African writers have pointed out, the ANC government has been largely negligent in protecting its African immigrants, even though its Secretary-General, Fikile Mbalula, recently issued a stinging rebuke of Zuma and anti-immigrant groups for their xenophobia. President Cyril Ramaphosa’s address to the nation, in which he largely focused on tough new measures to clamp down on illegal immigration rather than taking on the violent vigilante groups, was dismissed by civil rights groups as playing the game of the anti-immigrant groups (Ruiters 2026). While opposition parties back the xenophobic agenda of March and March to capture votes from the ANC, the ANC refuses to be tough on anti-immigrant violence for fear of losing those very votes. All is not lost, however, in the fight against xenophobia in South Africa because of its vibrant civil society. Julius Malema’s Economic Freedom Fighters (EFF) is implacably opposed to the wave of xenophobia sweeping across the country. There is also a large number of civil society groups actively campaigning against the phenomenon. Chief among them is the newly formed United Front, Siyafana Sonke Action Campaign (2026), of over 160 organisations. Reports of their activities include writing open letters to Ramaphosa, publicly condemning what they describe as ‘pogroms and forced removals’ and demanding the arrest of vigilante ringleaders. The campaign has called for the cancellation of the 30 June demonstrations and demanded an urgent meeting with the president. Another organisation, Lawyers for Human Rights (2026), works on injunctions to prevent vigilante groups from blocking foreigners from accessing hospitals and schools. It has described the government’s policy of forcing documented refugees into ‘verification processes’ while vigilantes watch as a form of unlawful profiling. And ACT Ubumbano propagates the view that poor South Africans should aim their anger at government corruption, not fellow Africans. Even an Indigenous community, the Tsonga-speaking people, has joined the protests against xenophobia because the anti-immigrant groups have included them among the immigrant population to be harassed (Mutandiro 2026). It seems, however, that xenophobic prejudice against African immigrants runs deep. This suggests that the ANC government has done a poor job of educating black South Africans about Africa’s stellar contributions to the struggle to dismantle apartheid. Mbeki noted in his lecture that Guinea under Sékou Touré taught its school children at all levels of the evils of apartheid and the pan-African resistance against it. South Africa can begin to repair its damaged reputation with the rest of Africa by teaching the social history of Africa’s contributions to the liberation of South Africa across its schools and tertiary institutions.